Theoretical substantiation of topping parameters without sugar beet head copying - Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич (My University, 2016)
Nowadays topper machines which cut beet tops without copying root heads via rotary topper and only after this heads are cuts individually by passive knife widely used in the world. However, with using this topping method significantly increases sugar-bearing plant material losses. Taking into account that sugar beet tops is effective raw material for receiving biogas, its collecting without loss is actual beet industry problem. However, when cutting tops from sugar beet heads with individual copying and collecting tops from each root crop head the topper productivity is significantly reduced, the design of the topping device becomes complicated, operational expenses considerably increase. Methods of mathematical modeling, programming and calculations on PC are used in the course of research. As a result of the conducted research the mathematical model of a cut without individual copying of root crop heads as well as algorithm are developed. This algorithm enables to determine the rational height of installation of the cutting device over the level of soil surface that in this turn provides minimum losses of beet tops. Dependence of sugar-bearing plant material losses and residues of beet tops on cut height without individual copying of root crops heads was experimentally defined. Comparison with theoretical calculations showed that in the range of working heights of a cut of 20-60 mm deviation does not exceed 1%.
Теоретическое обоснование параметров среза ботвы сахарной свеклы с головок корнеплодов без их копирования
Keywords: sugar beet; root crop heads; tops; mathematical model; cut without copying